Malawi : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Malawi. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2015)
This 2015 Article IV Consultation highlights that bold economic reforms undertaken in mid-2012 in Malawi transformed the policy environment and greatly improved the outlook of the economy. Over 2012-14, real GDP growth and inflation averaged 4.3 percent and 24.5 percent, respectively. The economic outlook remains difficult reflecting the negative impact of weather-related shocks, the ongoing suspension of budget support, persistently high inflation and weaker global demand which could hurt Malawi's exports. Real GDP growth is projected to fall by 2.7 percentage points to 3 percent in 2015.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet